TOWARDS A USAGE-BASED COGNITIVE PHONOLOGY - Gitten Kristiansen (International Journal of English Studies (IJES), 2006)
The usage-based conception of language is a major tenet in Cognitive Linguistics, but cognitive phonology has not yet been developed sufficiently in this direction. Often, phonemic analysis is carried out at the high level of abstraction of `a language´, disregarding rich patterns of languageinternal variation. This paper first argues that cognitive phonology must aim at a higher degree of descriptive refinement, especially in the direction of social variation. Then it goes on to examine the implications of a usage-based and multi-faceted model for a theoretical discussion of the phoneme as a prototype category.